Assessing the Efficiency of a Proposed Agrivoltaic System in Bangladesh to Ensure Multiple Uses of Land and Water (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
A new conceptual agrivoltaic system has been designed, developed, and tested in this study to assure multiple uses of land for energy and food production along with a Carbon Capturing Device (CCD), which is not yet practiced. Dust deposition on the solar panel of agrivoltaic system can impair power generation. As a result, regular cleaning of the solar panel is required for improved panel performance. However, dry cleaning is not always appropriate for effective cleaning when sticky materials, such as bird droppings or dirt, deposition on the panel. Depending on the size of the PV system, wet cleaning will take a large volume of water. Therefore, this study aimed to investigate the proposed agrivoltaic system to explore the potential of sustainable ways of utilizing water for multiple applications. In the outdoor experiment, the developed prototype was tested. The amount of provided and recovered water was determined. Recycled water was used to grow Napier grass, water spinach, and fish. Within one month, yields from vegetation and fish were 8 kg and 426 grams, respectively. In addition, research has been conducted using carbon sequestration techniques to construct a CCD utilizing algae and recycled water. A comparative study of water and algae scrubbing found that algae washing removed 9.10% more CO2 from the sample gas than water scrubbing. Additional biogas scrubbing experiments demonstrated that the developed algal CCD eliminated 78% of the undesired H2S from biogas. The study finds that deploying the combined production technique for power and food can give a mutual advantage. The effective application of the aforementioned method might help to accomplish the following Sustainable Development Goals: SDG 13- Climate Action; SDG 7-Affordable and Clean Energy. It can provide environmental and economic sustainability by producing clean energy and conserving water. It is obvious that more research in this area is necessary, and the outcomes for various crops and geographical regions of the country and further improvement scopes should be investigated to determine the potential of agrivoltaic farming in Bangladesh.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(2), 2022: P 33-41